Monitoring Evaluation of the Learning Process - Khoirunnisa; Juliadi; Nelfa Sari; Henny Septia Utami; Riyan Terna Kuswanto (Yayasan Zia Salsabila, 2024)
The learning process is a research theme that has constantly received attention from previous researchers. Given, that the learning process will determine the quality of learning outcomes. Previous research found that the learning process is highly dependent on the maturity of planning. On this basis, this study aims to carry out evaluation monitoring of the learning process. The setting of this research is located at the Faculty of Tarbiyah, Institut Agama Islam Negeri Curup. The approach used in this research is qualitative with descriptive study method. Furthermore, the data were obtained from interview method, participant observation and documentation study. The results of this study concluded that the standard operating procedures (SOP) became a reference for monitoring the evaluation of the learning process. In fact, the SOP becomes a form of learning planning maturity process. For this reason, the SOP products produced in this study can be a reference in efforts to strengthen systematic learning from the planning to evaluation stages.